2020
DOI: 10.1158/1940-6207.capr-19-0339
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Erlotinib and Naproxen Employing Pulsatile or Intermittent Dosing Profoundly Inhibits Urinary Bladder Cancers

Abstract: Daily dosing of either NSAIDs or EGFR inhibitors has been shown to prevent bladder cancer development in a N-butyl-(4-hydroxybutyl)nitrosamine (OH-BBN)-induced rat model. However, these inhibitors cause gastrointestinal ulceration and acneiform rash, respectively, limiting their continuous use in a clinical prevention setting. We studied chemopreventive efficacy of pulsatile dosing of EGFR inhibitor erlotinib (42 mg/kg BW, once/week) combined with intermittent or continuous low doses of the NSAID naproxen (30 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…In summary, the combination of an EGFR inhibitor and an NSAID is an excellent candidate for treatment of basal bladder cancer. We have confirmed these results in the OHBBN-induced bladder cancer model employing the combination of erlotinib and naproxen [21]. Furthermore, the combination erlotinib plus sulindac has proven highly effective clinically in an FAP trial [23] which should offer clear ideas regarding likely toxicities of such a combination.…”
Section: Discussionsupporting
confidence: 66%
“…In summary, the combination of an EGFR inhibitor and an NSAID is an excellent candidate for treatment of basal bladder cancer. We have confirmed these results in the OHBBN-induced bladder cancer model employing the combination of erlotinib and naproxen [21]. Furthermore, the combination erlotinib plus sulindac has proven highly effective clinically in an FAP trial [23] which should offer clear ideas regarding likely toxicities of such a combination.…”
Section: Discussionsupporting
confidence: 66%
“…We have shown that FKA preferentially inhibited the growth of HER2-overexpressing breast cancer cell lines (i.e., SKBR3 and MCF7/HER2) versus those with less HER2 expression (i.e., MCF7 and MDA-MB-468) through inhibition of Cdc2 and Cdc25C phosphorylation and downregulation of expression of Myt1 and Wee1 [ 22 ]. To more efficiently inhibit tumor growth in NMIBC, combination approaches of FKA with RAS-targeting drugs (e.g., sotorasib and salirasib) [ 23 , 24 ], FGFR-3 inhibitor (e.g., erdafitinib) [ 25 ], and EGFR inhibitors (e.g., erlotinib and gefitinib) [ 26 , 27 ] should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the treatment of bladder cancer is mostly a combination of surgery and chemotherapy. The most effective way to prevent postoperative recurrence of bladder cancer patients is to supplement the intravesical infusion of immunosuppressants or chemotherapy drugs after surgery, but the recurrence rate of the tumor after surgery is as high as 60-70% [22,23]. The severe side effects limit its clinical application.…”
Section: Discussionmentioning
confidence: 99%